2016
DOI: 10.4168/aair.2016.8.6.541
|View full text |Cite
|
Sign up to set email alerts
|

The Basophil Activation Test Is Safe and Useful for Confirming Drug-Induced Anaphylaxis

Abstract: The basophil activation test (BAT) has been suggested as a complementary method for diagnosing drug allergies. The aim of this study was to evaluate the clinical utility of this test in patients with drug-induced anaphylaxis. In total, 19 patients, all of whom had a history of moderate to severe anaphylaxis, were enrolled. None of the causative drugs had available in vitro tests or reliable skin tests; these drugs included, among others, first and second-generation cephalosporins, H2 blockers, and muscle relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…BAT was reported as useful in the diagnosis of quinolone hypersensitivity919 whereas some authors demonstrated contradictory results 14. BAT could be a useful option in the conditions that skin testing is not suitable for the drugs or for the hypersensitivity reactions like anaphylaxis 36. In addition, it is known that the usage of BAT is limited to some qualified and specialized centers 37.…”
Section: Discussionmentioning
confidence: 99%
“…BAT was reported as useful in the diagnosis of quinolone hypersensitivity919 whereas some authors demonstrated contradictory results 14. BAT could be a useful option in the conditions that skin testing is not suitable for the drugs or for the hypersensitivity reactions like anaphylaxis 36. In addition, it is known that the usage of BAT is limited to some qualified and specialized centers 37.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IDT using levodropropizine induced a positive response (A/H ratio of 3+ at 0.1 mg/mL). To confirm the diagnosis of anaphylaxis due to levodropropizine, we planned BATs instead of OPTs, according to the previously described method 4. We found a significant up-regulation of CD63 expression after stimulation with levodropropizine (Figure).…”
Section: Case Reportmentioning
confidence: 93%
“…Additionally, during anaphylaxis, proteins such as CD63 and CD203c become newly or increasingly expressed on the surface of basophils. These can be detected by flow cytometry, which forms the basis of experimental drug‐induced basophil activation tests 51. In future, basophil activation tests may replace skin tests as the gold standard for making a definitive diagnosis of anaphylaxis, as this assay has the advantage of not being associated with the risk of inducing anaphylaxis during the test 52.…”
Section: Confirmation Of Anaphylaxis Trigger(s)mentioning
confidence: 99%